(untitled) (Bioscience Journal, 2017)
execute the face validation of the educative manual for head and neck cancer patients submitted to radiotherapy. Methodological and descriptive research. The sample consisted of 11 patients, divided in four groups according to the instruction level. An Agreement Rate of at least 80% was considered to guarantee the validation of the material with regard to its semantic analysis. The items addressed in the evaluation tool of the educative manual were divided in five blocks: objectives, organization, writing style, appearance and motivation. Only one item, related to the cover of the material, obtained an Agreement Rate < 80% and was reformulated based on the participants’ suggestions. All other items were considered appropriate and/or totally appropriate in the five blocks proposed: objectives - 100%, structure and presentation - 93.93%, writing style - 95.45%, appearance - 97.72%, and motivation - 93.50%. The analysis of the face validation of the educative manual proposed demonstrated that it is apt for use as a guide during the nursing consultation, in order to support nursing care for head and neck cancer patients submitted to radiotherapy.